2019
DOI: 10.1002/mp.13866
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Comprehensive evaluation and implementation of two independent methods for beam monitor calibration for proton scanning beam

Abstract: Purpose To clinically implement and comprehensively evaluate two independent methods for beam monitor calibration of scanning proton beam. Methods Seven proton energies that represent the lowest to highest energy proton beams were selected. Single energy layer circular fields of diameter 15 cm with 2.5 mm spot spacing and 10 times of repainting (FS15cm) were designed for all energies. The effective measurement points of Bragg peak chamber (BPC), advanced Markus chamber (AMC) and farmer chamber (FC) were all al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(76 reference statements)
1
12
0
Order By: Relevance
“…The observed fluctuations for the Bragg peak chamber's temporal drift prevented the use of a single linear fit for a baseline correction. Recently it was reported that the homogeneity of Bragg peak chambers is not uniform 46,47 and thus effects seen in this study could be influenced by its heterogeneous response. However, as the observed magnetic field dependency was small and the Bragg peak chamber air gap variance was reported to vary by 5%, such an effect would probably not be noticeable.…”
Section: Discussionmentioning
confidence: 78%
“…The observed fluctuations for the Bragg peak chamber's temporal drift prevented the use of a single linear fit for a baseline correction. Recently it was reported that the homogeneity of Bragg peak chambers is not uniform 46,47 and thus effects seen in this study could be influenced by its heterogeneous response. However, as the observed magnetic field dependency was small and the Bragg peak chamber air gap variance was reported to vary by 5%, such an effect would probably not be noticeable.…”
Section: Discussionmentioning
confidence: 78%
“…A single‐layer field constitutes of a single nominal‐energy beam covering a certain lateral area with equal‐energy spots that are equidistant in both orthogonal directions and in which the same number of particles is delivered per spot. An alternative method using a large‐area plane‐parallel ionization chamber has also been proposed but has not been as well established 5,7–10 . Other efforts have focused on the calculation 11–13 or experimental determination 14–16 of beam quality correction factors at shallow depth.…”
Section: Introductionmentioning
confidence: 99%
“…For the single‐layer method, it has been proposed that a Farmer‐type ionization chamber (IC) or a plane‐parallel ionization chamber (PPIC) can be used for the determination of absorbed dose to water in reference conditions 5,8,10 . Since for most of the clinical proton beam energy range, there are depth dose gradients present at shallow depths, preference may be given to the use of a PPIC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations